Safeguards Assessments : Review of Experience. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The safeguards assessments policy was introduced in March 2000 to provide reasonable assurance that central banks have adequate financial control systems in place to manage their resources and Fund disbursements. The safeguards policy's main objective is to minimize the possibility of misreporting or misuse of Fund resources associated with the Fund's lending activities. Safeguards assessments apply to all member countries that have a Fund arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet